Intervenção cirúrgica e tratamento fisioterapêutico no pós-operatório do câncer de mama: efeitos na cinemática escapular, morbidade dos membros superiores e qualidade de vida - Ribeiro, Ivana Leão (2017)
The major dysfunctions of the upper extremity related to postoperative (PO) breast cancer, such as functional limitations and muscle weakness, have been studied. The three-dimensional (3D) scapula movement may be altered in the short and long term, but conclusive studies on this subject are still lacking. Although upper extremity rehabilitation programs are recommended after surgery, the great variability in intervention protocols associated with the lack of specificity of training hinders referral to clinical practice. Thus, the general objectives of this Doctorate project were: to evaluate the 3D scapula movement during both elevation and lowering of the arm of individuals treated by breast cancer surgery and to compare with a healthy and asymptomatic control group for shoulder pain; to evaluate the effectiveness of early physiotherapy interventions in the preservation of upper limb function; to investigate the short-term effects of surgery on kinematics and scapuloumeral rhythm after a physical therapy program in the immediate postoperative period. The thesis gave rise to three studies: 1 - Case-control study of 3D kinematics of the scapula, 2 - Systematic review on physiotherapy in the immediate PO, 3 - A series of cases of the short-term effects of surgery on kinematics and rhythm after a physiotherapy program in the immediate postoperative period. A total of 47 women (Study 1, n = 21 surgery group and n = 21 control group, Study 3, n = 05) participated in this study. The 3D kinematics were collected using superficial electromagnetic sensors during arm movement in the scapular plane, the range of motion (ROM) and shoulder muscle strength were evaluated by a digital inclinometer and manual dynamometer, respectively. Pain intensity, upper limb function, and quality of life were assessed using the Visual Analogue Scale (EVA), Disabilities of the arm, shoulder and hand questionnaire (DASH), 36-item Short Form Health Survey (SF36), respectively. A series of databases were consulted to select the studies relevant to the review, based on the Cochrane recommendations, the PEDro scale was used to verify the methodological quality of the included studies and the GRADE was used to analyze the synthesis of evidence (Study 2). Data from studies 1 and 3 were analyzed according to the comparisons between groups (Study 1) and within groups (Studies 1 and 3), using the SPSS version 21 program and the Cohen d index to calculate the effect size. The main results of study 1 were: lower superior rotation of the scapula (120º), lower ROM and shoulder strength, in addition, high scores of EVA, DASH and SF36 in the surgery group; study 2: moderate level of evidence regarding the efficacy of both isolated and associated ROM exercises to muscle strength training for shoulder ROM gain; study 3: lower upward rotation and more anterior scapula tilt along the arm movement, decrease of the scapulohumeral rhythm, high EVA and DASH scores during the evaluations; After the surgery of the breast cancer functional alterations of the scapular kinematics, ROM and shoulder strength, scapuloumeral rhythm as well as self-report of pain and incapacities are evidenced. Early rehabilitation of the upper limb after surgery should be focused primarily on the preservation of shoulder ROM. Future randomized and controlled clinical trials should investigate the efficacy of physiotherapeutic treatment to restore upper limb function, especially considering periods of long-term treatment.